How do patients experience stress caused by hospitalisation and how do nurses perceive this stress experienced by patients? A comparative study - Kotrotsiou, Evangelia; Theodosopoulou, Eleni; Raftopoulos, Vasilios (My University, 2001)
It has been acknowledged that, in general, stress caused by hospitalisation and hospital care may hinder patient recovery and in some cases it may cause potentially life-threatening psychological changes. Hospitalisation and subsequent treatment and medical care constitute a period of anxiety for the patients and a severe anxiety-causing situation. This fact has been confirmed by a large number of researches studying many different kinds of hospital care.1 Many factors were reported to contribute to this anxiety, including those relating to an illness such as pain, anxiety or improvement and recovery, and factors relating to hospital stay such as sleeping in a strange bed or sharing a hospital room with others.
Keywords: Patients; Nurses; Hospitality; Hospital care